Alagille Syndrome: A Novel Mutation in JAG1 Gene - Fischetto, Rita; Palmieri, Viviana V.; Tripaldi, Maria E.; Gaeta, Alberto; Michelucci, Angela; Delvecchio, Maurizio; Francavilla, Ruggiero; Giordano, Paola (Frontiers in Pediatrics, 2019)
Alagille syndrome is an autosomal dominant multisystem disorder with variable phenotypic penetrance, caused by heterozygous mutations in JAG1 or NOTCH2, encoding for the components of the Notch signaling pathway.In this paper, we described a novel mutation not yet reported in literature. This 3-years old male child was referred to our Clinical Genetics Unit because of delayed psychomotor development, systolic murmur, dysmorphic facial features and hypertransaminasemia. The novel JAG1heterozygous c.2026delTvariant in exon 16was found. JAG1 mutations are classified as proteintruncating and non-protein truncating, without any genotype-phenotype correlation. The detected mutation determines a stop codon (p.Cys676AlafsTer67) in the gene sequence, encoding a truncated protein. Our report broadens the spectrum ofJAG1 gene mutations.